Smoking Behavior in Health Students in Jayapura City - Ayomi, Mina Blandina (Universitas Airlangga, 2024)
Background: The 2021 Global Adult Tobacco Survey (GATS) showed an increase in the number of adult smokers by 8.8 million, namely from 60.3 million in 2011 to 69.1 million in 2021. Although the prevalence of smoking in Indonesia has decreased from 1 8% to 1.6, Papua Province's percentage of smoking among the population aged 15 years from 2021-2023 is 24.91%, decreasing to 22.22% in 2023 to 22.3%. Aims: This research is to determine the perception of smoking among health students in Jayapura City. Method: The research used a descriptive survey with samples from 100 health students from various universities in Jayapura City, the research location, from June to September 2023. Data were collected using a questionnaire consisting of several questions. The data were analyzed univariately, displayed in table form, and narrated. Results: There were 34 respondents (34%) smoking activities and 66 respondents (66%) who did not. This type of cigarette is smoked 100% cigarettes. The number of cigarettes smoked was 4-6 cigarettes; there were 25 respondents (73.5%) and nine respondents (26.5%) 7-10 cigarettes. Twenty-nine respondents (85.3%) smoked outdoors, and five respondents (14.7%) were indoors. Length of smoking ³ three years, there were 30 respondents (88.2%), and for less <than one year, there were four respondents (11.8%). The reason for smoking was to relieve stress for 25 respondents (73.5%) and for hanging out with friends for nine respondents (26.5%). Plans to stop smoking: 27 respondents (79.5%) and 7 respondents (20.5%) did not stop smoking. Conclusion: It can be concluded, that the reason for smoking is because of stress and having many problems, but more respondents want to stop smoking. Efforts and good intentions can stop smoking among health students as agents of societal change.